MATHEMATICAL MODELING OF THE COMBUSTION PROCESS AND FORMATION OF NOXIOUS SUBSTANCES IN A DIESEL ENGINE COMBUSTION CHAMBER - Avramenko, A.; Авраменко, А. М.; Авраменко, А. Н. (Харьковский национальный автомобильно-дорожный университет, 2016)
There were considered the main stages of mathematical modeling of carburation, combustion and formation of noxious substances in the combustion chamber of a four-stroke diesel engine operating at maximum torque in a 3D nonstationary problem statement. The combustion products composition was evaluated for such components as NO and solid particles.
МАТЕМАТИЧНЕ МОДЕЛЮВАННЯ ПРОЦЕСУ ЗГОРЯННЯ ТА ФОРМУВАННЯ ШКІДЛИВИХ РЕЧОВИН У КАМЕРІ ЗГОРЯННЯ ДИЗЕЛЯ
МАТЕМАТИЧЕСКОЕ МОДЕЛИРОВАНИЕ ПРОЦЕССА СГОРАНИЯ И ФОРМИРОВАНИЯ ВРЕДНЫХ ВЕЩЕСТВ В КАМЕРЕ СГОРАНИЯ ДИЗЕЛЯ
Keywords: diesel fuel combustion; flame temperature; Zeldovich thermal mechanism; noxious substances; solid particals; дизельне паливо; горіння; температура; камера згоряння; токсичні речовини; дизельное топливо; горение; температура; камера сгорания; токсичные вещества; 621.43